2014
DOI: 10.1128/jb.01259-13
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Apurinic/Apyrimidinic Endonucleases Nfo and ExoA with the DNA Integrity Scanning Protein DisA in the Processing of Oxidative DNA Damage during Bacillus subtilis Spore Outgrowth

Abstract: Oxidative stress-induced damage, including 8-oxo-guanine and apurinic/apyrimidinic (AP) DNA lesions, were detected in dormant and outgrowing Bacillus subtilis spores lacking the AP endonucleases Nfo and ExoA. Spores of the Δnfo exoA strain exhibited slightly slowed germination and greatly slowed outgrowth that drastically slowed the spores' return to vegetative growth. A null mutation in the disA gene, encoding a DNA integrity scanning protein (DisA), suppressed this phenotype, as spores lacking Nfo, ExoA, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 33 publications
0
43
0
2
Order By: Relevance
“…It was also observed that the DAC activity of DisA is strongly inhibited by the presence of non-standard DNA secondary structures like Holliday junctions (9). A recent study emphasized a function of DisA in controlling genome replication during outgrowth of B. subtilis spores to prevent propagation of damaged DNA to the germinating cells (12). Meanwhile, homologs of DisA have been identified in several other bacteria like Mycobacterium tuberculosis (13)(14)(15).…”
mentioning
confidence: 99%
“…It was also observed that the DAC activity of DisA is strongly inhibited by the presence of non-standard DNA secondary structures like Holliday junctions (9). A recent study emphasized a function of DisA in controlling genome replication during outgrowth of B. subtilis spores to prevent propagation of damaged DNA to the germinating cells (12). Meanwhile, homologs of DisA have been identified in several other bacteria like Mycobacterium tuberculosis (13)(14)(15).…”
mentioning
confidence: 99%
“…1A). DisA is involved in the control of DNA integrity, and the activity of this enzyme is controlled by a protein-protein interaction with the DNA methyltransferase RadA, as first observed for Mycobacterium smegmatis (13)(14)(15). CdaA is the most widespread diadenylate cyclase, and it is the only such enzyme in pathogenic firmicutes.…”
mentioning
confidence: 99%
“…This interaction leads to a functional change of downstream effector proteins and enables control of specific cellular pathways. Although it was only recently identified as a second messenger, c-di-AMP was found to have central importance in numerous bacterial functions including stress responses, antibiotic resistance, cellular morphology, bacterial growth, and virulence (5)(6)(7)(8)(9)(10)(11)(12). Also, c-di-AMP secretion by Listeria monocytogenes, Mycobacterium tuberculosis, and Chlamydia trachomatis during infection induces an IFN-␤-mediated host immune response (13)(14)(15).…”
mentioning
confidence: 99%